Gepotidacin for the Treatment of Uncomplicated Urogenital Gonorrhea: A Phase 2, Randomized, Dose-Ranging, Single-Oral Dose Evaluation. (2nd April 2018) - Taylor, Stephanie N; Morris, David H; Avery, Ann K; Workowski, Kimberly A; Batteiger, Byron E; Tiffany, Courtney A; Perry, Caroline R; Raychaudhuri, Aparna; Scangarella-Oman, Nicole E; Hossain, Mohammad; Dumont, Etienne F
Abstract : In this phase 2 study, single oral doses of gepotidacin were ≥95% effective for bacterial eradication in culture-proven uncomplicated urogenital gonorrhea. New antibiotics for drug-resistant Neisseria gonorrhoeae are urgently needed. With additional evaluation, gepotidacin may provide an alternative therapeutic option. Abstract: Background: In this phase 2 study, we evaluated the efficacy and safety of oral gepotidacin, a novel triazaacenaphthylene bacterial type II topoisomerase inhibitor, for the treatment of uncomplicated urogenital gonorrhea. Methods: Adult participants with suspected urogenital gonorrhea were enrolled and completed baseline (day 1) and test-of-cure (days 4–8) visits. Pretreatment and posttreatment urogenital swabs were collected for Neisseria gonorrhoeae (NG) culture and susceptibility testing. Pharyngeal and rectal swab specimens were collected if there were known exposures. Participants were stratified by gender and randomized 1:1 to receive a 1500-mg or 3000-mg single oral dose of gepotidacin. Results: The microbiologically evaluable population consisted of 69 participants, with NG isolated from 69 (100%) urogenital, 2 (3%) pharyngeal, and 3 (4%) rectal specimens. Microbiological eradication of NG was achieved by 97%, 95%, and 96% of participants (lower 1-sided exact 95% confidence interval bound, 85.1%, 84.7%, and 89.1%, respectively) for the 1500-mg, 3000-mg, and combined dose groups, respectively. Microbiological cure was achieved in 66/69 (96%) urogenital infections. All 3 failures were NG isolates that demonstrated the highest observed gepotidacin minimum inhibitory concentration of 1 µg/mL and a common gene mutation. At the pharyngeal and rectal sites, 1/2 and 3/3 NG isolates, respectively, demonstrated microbiological cure. There were no treatment-limiting adverse events for either dose. Conclusions: This study demonstrated that single, oral doses of gepotidacin were ≥95% effective for bacterial eradication of NG in adult participants with uncomplicated urogenital gonorrhea. Clinical Trials Registration: NCT02294682.